2010
DOI: 10.1002/rcs.359
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional image‐guided placement of percutaneous pedicle screws without the use of biplanar fluoroscopy or Kirschner wires: technical note

Abstract: Percutaneous pedicle screws can be placed accurately and safely using 3D image guidance without the use of K-wires. Little to no radiation exposure to the surgeon or OR staff occurs with this technique. No complications occurred in this study as a result of screw placement or image guidance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…19,25,42,44,47,49 In the present study using the K-wireless percutaneous screw system with biplanar fluoroscopy, 87 of 90 screws were placed within the confines of the pedicle for an overall breach rate of 3.3%, which is consistent with other published reports. 30,32,36,39,42,44,47,49 In further examining the 3 pedicle breaches, 2 were less than 2 mm. It has been demonstrated that in the lumbar spine, there is a 2-mm "safe zone" that represents the epidural space in which there is little risk to the spinal cord or cauda equina.…”
Section: 83441mentioning
confidence: 97%
See 1 more Smart Citation
“…19,25,42,44,47,49 In the present study using the K-wireless percutaneous screw system with biplanar fluoroscopy, 87 of 90 screws were placed within the confines of the pedicle for an overall breach rate of 3.3%, which is consistent with other published reports. 30,32,36,39,42,44,47,49 In further examining the 3 pedicle breaches, 2 were less than 2 mm. It has been demonstrated that in the lumbar spine, there is a 2-mm "safe zone" that represents the epidural space in which there is little risk to the spinal cord or cauda equina.…”
Section: 83441mentioning
confidence: 97%
“…1,21,30 The use of fluoroscopy exposes the patient, surgeon, and operating room staff to ionizing radiation. In fact, fluoroscopically assisted open thoracolumbar pedicle-screw placement exposes the spine surgeon to radiation dose rates up to 10-12 times greater than other, nonspinal musculoskeletal procedures.…”
Section: 83441mentioning
confidence: 99%
“…10 Moreover, these K-wires may break or bend during the procedure, reducing the accuracy of cannulated screw placement and possibly damaging equipment. 21 None of the patients in our study, who were treated without K-wires, suffered intraoperative or postoperative vascular or neurological complications. Only one screw was malpositioned in this series, as a result of a suboptimal trajectory during placement, and there was no need for repositioning.…”
Section: Discussionmentioning
confidence: 73%
“…The use of cbCT-based image guidance for percutaneous pedicle screw placement has been reported. 1,12,25 Obviously, the surgeon is not exposed to radiation during screw placement in open or minimally invasive cbCT-based, image-guided spinal surgery, as the surgeon is navigating from the intraoperative cbCT scan, and no active fluoroscopy is used.…”
Section: Discussionmentioning
confidence: 99%